Menjelajahi Terjemahan Bahasa Waktu Nyata (RLT) dalam Pembelajaran Bahasa Inggris: Meningkatkan Komunikasi di Thailand - Nilobol, Phatphong; Dhammabhissamai, Phrakru; Chusukserm, Thanakorn (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
This article discusses whether real-time language translation tools, such as Google Translate or similar online applications, prove effective in English language education, particularly in Thailand. Here, although English proficiency grows increasingly vital in this new globalizing world, students in Thailand are still falling behind in their efforts to master the language. Time-honored teaching methods generally have failed to address the issues at hand, with the greatest problems occurring where pupils have little exposure at school. AI-powered real-time language translation may be a solution to that problem by providing immediate translations that will help bridge the gap created by current abilities and requirements imposed by the need to learn the English language. This article aims to discuss how these tools influence the process of learning, including overcoming language barriers. It also delves into the perceptions of educators and learners in the use of such tools within a classroom. To gain insight, it will conduct some qualitative interviews with two practicing English teachers and two students who have had practical experience using real-time translation tools in their learning environment. These interviews will provide valuable insights into the practical applications, benefits, and challenges associated with the use of AI-powered translation tools in teaching the English language. Indeed, the results from this study show that real-time translation tools can enhance students' comprehension and confidence in using English. Teachers said that this scaffolding was particularly helpful in reaching complex texts and unknown lexis with a minimum loss of frustration and anxiety linked with language learning. For the students, on the other hand, the tools provided immediate support for their most pressing needs, thus enabling them to take part in class discussions and assignments with more enthusiasm. This means that the students were able to learn from their mistakes immediately with real-time translation tools. It also helped reinforce the understanding of the language in their minds. However, the study has some drawbacks of using real-time translation tools. Teachers and students alike are concerned with the accuracy of the translations, especially with idiomatic expressions or cultural nuances that AI would not understand. There is also a chance that they will become overly reliant on these tools at the expense of internal development of language problem-solving and critical thinking skills. Keywords: Real-time language translation (RLT), English, Thai students, CLT pedagogy